Efficacy and Safety of Concomitant Chemoradiotherapy with Cisplatin and Docetaxel in Patients with Locally Advanced Squamous Cell Head and Neck Cancers - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2013)
Background: Chemoradiation (CRT) using cisplatin-based regimens has become the standard of care in the treatment of squamous cell head and neck cancers (SCHNC). The impact of taxanes as radiosensitizing agents with concurrent CRT regimens is unknown. We therefore retrospectively evaluated the efficacy and tolerability of a weekly cisplatin+docetaxel combination with CRT in locally advanced SCHNC. Methods: Sixty-six patients with locally advanced SCHNC (39.4% stage IV, 53% stage III, and 7.6% stage II) were assessed retrospectively. Total radiation dose to the PTV of gross disease (primary and/or node) was 70 Gy/35 fractions, 5 fractions per week. Minimum doses of 60 Gy and 50 Gy were administered to PTVs of elective high risk and low risk disease, respectively. Chemotherapy (CT) consisted of weekly cisplatin (20 mg/m(2))+docetaxel (20 mg/m(2)) concurrently with RT. Results: The median age of the patients was 58 years (range, 32-77). Objective response rate was 83.3%. The 2-year progression-free survival (PFS) and overall survival (OS) were 75.7% and 78.3%, respectively. The most common grade 3 and 4 toxicities were mucositis (36.4%), nausea and vomiting (12.1%), neutropenia (4.5%). Conclusion: Weekly cisplatin and docetaxel concurrent with RT for locally advanced SCHNC was found tolerable with high efficacy.
Keywords: Squamous cell head and neck cancers; chemoradiotherapy; cisplatin; docetaxel; safety; CONCURRENT RADIATION-THERAPY; PHASE-II TRIAL; INDUCTION CHEMOTHERAPY; ORGAN PRESERVATION; WEEKLY PACLITAXEL; RANDOMIZED-TRIAL; BOOST RADIATION; ONCOLOGY-GROUP; STAGE-III; RADIOTHERAPY